Cortical GABA in Subjects at Ultra-High Risk of Psychosis: Relationship to Negative Prodromal Symptoms - Modinos, Gemma; Şimşek, Fatma; Horder, Jamie; Bossong, Matthijs; Bonoldi, Ilaria; Azis, Matilda; Perez, Jesus; Broome, Matthew; Lythgoe, David J; Stone, James M; Howes, Oliver D; Murphy, Declan G; et al. (The international journal of neuropsychopharmacology, 2018)
Whilst robust preclinical and postmortem evidence suggests that altered GABAergic function is central to the development of psychosis, little is known about whether it is altered in subjects at ultra-high risk of psychosis, or its relationship to prodromal symptoms. Twenty-one antipsychotic naïve ultra-high risk individuals and 20 healthy volunteers underwent proton magnetic resonance imaging at 3T. Gamma-aminobutyric acid levels were obtained from the medial prefrontal cortex using MEGA-PRESS and expressed as peak-area ratios relative to the synchronously acquired creatine signal. Gamma-aminobutyric acid levels were then related to severity of positive and negative symptoms as measured with the Community Assessment of At-Risk Mental States. Whilst we found no significant difference in gamma-aminobutyric acid levels between ultra-high risk subjects and healthy controls (P=.130), in ultra-high risk individuals, medial prefrontal cortex GABA levels were negatively correlated with the severity of negative symptoms (P=.013). These findings suggest that gamma-aminobutyric acidergic neurotransmission may be involved in the neurobiology of negative symptoms in the ultra-high risk state.